Can Fintech Foster Competition in the Banking System in Latin America and the Caribbean?. (IMF Working Papers; Working Paper ;, 2021)
This paper revisits the competitive environment of the banking system in Latin America and the Caribbean (LAC) and investigates the early impact of fintech development in the region thus far. Against the backdrop of high net interest margins (NIMs) and limited financial depth in the region, panel regressions broadly confirm results of existing literature on the association of NIMs with the changes in the financial sector structure, including market concentration, administrative costs, and foreign banks, although differences between domestic and foreign banks narrowed after the 2008-09 Global Financial Crisis. Difference-in-difference regressions and case studies on Brazil and Mexico suggest that fintech is associated with a reduction in NIMs and defensive responses by incumbent banks that benefit consumers. The case studies also shed light on regulatory approaches and prudential considerations in fostering financial innovation and banking sector competition.